2018
DOI: 10.1007/s13205-018-1382-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Chilli veinal mottle virus infecting different chilli landraces in North East India indicates the possibility of transboundary movement of virus

Abstract: Diverse chilli genetic resources of North East India occupy a unique niche in the Nation's chilli gene pool. Widely cultivated chilli landraces (King chilli: , bird eye chilli: and ) of North East India in general and Manipur in particular suffer from decline complex due to high incidence of viral diseases. With this background and the known prominent distribution of (ChiVMV) in Asian region, we studied its prevalence and association with diverse symptoms of chilli landraces. Molecular indexing of samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…High incidence of viral infection as recorded through visual observations of symptoms and recent report of ChiVMV infection on Naga chilli from Meghalaya indicated the possibility of its association with chilli decline in the NE region (Banerjee et al 2014). Sanabam et al, 2018 reported that, NE region being contagious to the Eastern Asian region provided a strong base for the possible prevalence of pathogenically and genetically diverse ChiVMV isolates. Previous researches revealed genetic heterogeneity among the characterized ChiVMV isolates using CP gene fragment might be due to the strong selective constraint on CP protein (King et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…High incidence of viral infection as recorded through visual observations of symptoms and recent report of ChiVMV infection on Naga chilli from Meghalaya indicated the possibility of its association with chilli decline in the NE region (Banerjee et al 2014). Sanabam et al, 2018 reported that, NE region being contagious to the Eastern Asian region provided a strong base for the possible prevalence of pathogenically and genetically diverse ChiVMV isolates. Previous researches revealed genetic heterogeneity among the characterized ChiVMV isolates using CP gene fragment might be due to the strong selective constraint on CP protein (King et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Different researches have shown over time that the crop is susceptible to different viruses which include Cucumber mosaic virus (CMV), Potato virus Y (PVY) (Talukdar et al, 2015;Baruah et al, 2016), Tomato Spotted Wilt Virus (TSWV) (Talukdar et al, 2015), Chilli leaf curl virus (ChLCV) ( Talukdar et al, 2015;Baruah et al, 2016) and Groundnut Bud Necrosis Virus (GBNV) (Baruah et al, 2016). Bhut jolokia has also been found to be susceptible to Chilliveinal mottle virus as reported from Meghalaya (Sanabam et al, 2018;Banerjee et al, 2014). The plants are at times infected by a single virus or collectively by different viruses thereby forming a viral complex (Baruah et al, 2016) which reduces the production and productivity to greater extent.…”
Section: Introductionmentioning
confidence: 98%
“…Viral diseases have always been a major constraint to chilli production and productivity worldwide [ 7 , 8 , 9 , 10 ]. At least 65 viruses have been reported to infect the chilli worldwide [ 11 ]; 24 among them occur under natural infection, and the rest occur under experimental conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…in the Indian subcontinent [ 13 ]. The NER of India has recorded a widespread prevalence and high incidence of viral diseases on all the cultivated chilli landraces (King chilli and bird’s eye chilli) due to the favourable environmental conditions prevailing throughout the growing seasons [ 7 , 14 ]. A thorough identification through the accurate detection of these viral diseases is the only means of carving out effective management measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation